2022
DOI: 10.1371/journal.pgph.0000598
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the adult HIV testing services screening tool to predict positivity yield in Zimbabwe, 2022

Abstract: HIV positivity yield declined against increasing testing volumes in Zimbabwe, from 20% (1.65 million tests) in 2011 to 6% (3 million tests) in 2018. A screening tool was introduced to aid testers to identify clients likely to obtain a positive diagnosis of HIV. Consequently, testing volumes declined to 2.3 million in 2019 but positivity declined to 5% prompting the evaluation and validation of the tool to improve its precision in predicting positivity yield. A cross-sectional study was conducted. Sixty-four si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…This study and research from other countries [ 12 ] show that screening tools could reduce testing volumes by 24%; hence, apparently saving the cost per HIV-positive case identified, screening in the current study resulted in a marginal increase in positivity rate from 3.71% to 4.5%. Of more concern is the number of clients who were misclassified as ineligible for HIV testing, even though they were HIV positive and they were willing to test for HIV.…”
Section: Discussionmentioning
confidence: 51%
“…This study and research from other countries [ 12 ] show that screening tools could reduce testing volumes by 24%; hence, apparently saving the cost per HIV-positive case identified, screening in the current study resulted in a marginal increase in positivity rate from 3.71% to 4.5%. Of more concern is the number of clients who were misclassified as ineligible for HIV testing, even though they were HIV positive and they were willing to test for HIV.…”
Section: Discussionmentioning
confidence: 51%
“…Since 2016, the HTS programme has been pursuing targeted testing as an approach to reduce testing volumes, increase efficiency in HIV testing and enhance the identification of people living with HIV, to enrol them on life-long Antiretroviral Therapy (ART). Eligibility for HIV testing is done using a validated Screening algorithm [17]. In this algorithm, high-risk individuals are offered provider-delivered testing whilst those screened out are offered HIVST kits for self-screen.…”
Section: Methodsmentioning
confidence: 99%
“…First, patients who were screened for their risk for HIV infection before testing scored a high positivity ratio of 8.5% compared with those who were not screened (5.5%). The risk screening was done using a standardized screening algorithm which is part of standard service delivery by the country, in determining eligibility for an HIV test [17]. Further, the screened patients contributed as high as 75% of the overall positivity obtained, when the calculation combined with those not screened.…”
Section: Interpretation Of Key Findingsmentioning
confidence: 99%
“…We applied objectivist and constructivist attributes of the Grounded theory and adapted them to suit our context. This facilitated the application of the comparative methodology that provided systematic guidance for gathering, synthesizing, analyzing, and conceptualizing qualitative data to understand health workers' perspectives on the use of screening tools in HIV testing [6]. The adaptation of the Grounded theory is illustrated in Figure 1.…”
Section: Study Design and Theoretical Frameworkmentioning
confidence: 99%
“…During the evaluation and validation exercise, it was anticipated that the positivity yield would decline since no screening was being done (both screened-in and screened-out clients were tested) in contrast with before the exercise when the screening tool guided eligibility for testing. However, it was noted with concern that a positivity yield of 7.53% was documented during the evaluation comparable with 7.68%, which was documented at the same facilities a month before the evaluation exercise [6]. This finding strongly suggested that either the tool was not being routinely utilized as expected, or that the tool was not effective in its determination of eligibility for testing.…”
Section: Introductionmentioning
confidence: 97%